Integration of Tradition-Based Digital Storytelling Using Artificial Intelligence: Paulo Freire’s Perspective and Pancasila in the Learning Process - Said, Ratna (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The purpose of this study is to integrate Paulo Freire’s ideas and Pancasila into the learning process of digital storytelling, which is rooted in cultural traditions and enhanced by artificial intelligence. It is expected that by combining Freire’s thought with the values embedded in the Pancasila Student Profile, education can serve as a tool to empower future generations, not only to develop intelligence but also to cultivate the courage to defend social justice and diversity. To obtain theoretical data, this research employs a qualitative approach and uses literature review techniques to examine and compare various sources. Data were collected from articles and scholarly journals relevant to the research objectives. The findings indicate that Paulo Freire’s ideas and Pancasila continue to hold significant value and can be applied in modern education, which emphasizes both technology and humanity. Freire’s and Pancasila’s principles of “Education for Liberation” can be sustained within Indonesia’s educational system through the use of technology that supports educational principles, such as individualized learning and collaborative learning. For the advancement of contemporary education, the principles of freedom, responsibility, and collaboration upheld by Paulo Freire and Pancasila provide a valuable foundation.